The Kuvan® adult maternal paediatric European registry (KAMPER) multinational observational study: baseline and 1-Year data in phenylketonuria patients responsive to sapropterin - Trefz, Friedrich K.; Muntau, Ania; Lagler, Florian Bartholomäus; Moreau, Flavie; Alm, Jan; Burlina, Alberto; Rutsch, Frank; Bélanger-Quintana, Amaya; Feillet, François (JIMD reports, 2015)
Introduction: Sapropterin dihydrochloride (Kuvan®), a synthetic 6R-diastereoisomer of tetrahydrobiopterin (BH4), is approved in Europe for the treatment of patients aged ≥4 years with hyperphenylalaninaemia (HPA) due to BH4-responsive phenylalanine hydroxylase (PAH) deficiency, in conjunction with a phenylalanine-restricted diet, and also for the treatment of patients with BH4 deficiency. Aims/methods: KAMPER is an ongoing, observational, multicentre registry with the primary objective of providing information over 15 years on long-term safety of sapropterin dihydrochloride treatment in patients with HPA. Here we report initial data on characteristics from patients recruited by the time of the third interim analysis and results at 1 year. Results: Overall, 325 patients from 55 sites in seven European countries were included in the analysis: 296 (91.1%) patients with PAH deficiency (median [Q1, Q3] age, 10.3 [7.2, 15.0] years) and 29 (8.9%) with BH4 deficiency (12.8 [6.6, 18.9] years). Fifty-nine patients (18.2%) were aged ≥18 years; 4 patients were pregnant. No elderly patients (aged ≥65 years) or patients with renal or hepatic insufficiency were enroled in the study. Twelve-month data were available for 164 patients with PAH deficiency and 16 with BH4 deficiency. No new safety concerns were identified as of May 2013. Conclusions: Initial data from KAMPER show that sapropterin dihydrochloride has a favourable safety profile. Registry data collected over time will provide insight into the management and outcomes of patients with PAH deficiency and BH4 deficiency, including long-term safety, impact on growth and neurocognitive outcomes and the effect of sapropterin dihydrochloride treatment on populations of special interest.
Gesehen am 06.07.2020